Efforts to Overcome Truancy Behavior in Students with Biblio-Counseling (Studies in Class IX C SMP Negeri Wonomulyo) - Muhammad Junaedi Mahyuddin; Fitriyanti Sulaiman; Handayani Sura; Aisyah Suryani; Muliyadi Muliyadi; M. Yasdar; Amien Wahyudi (Budapest International Research and Critics University, 2021)
This research is a classroom action research (PTBK). The purpose of this study is to overcome truancy behavior of students in class IX C at SMP Negeri 1 Wonomulyo. The research subjects were taken by using a purposive sampling approaches. The number of research subjects is 8 students with truant behavior varied from 3 to 9 times. The results showed that the truant behavior of students after the first cycle of action was reduced to 0. Thus efforts to overcome student truancy behavior can be done by using biblio-counseling.